The Influence Of Promotion On Purchasing Decisions Through Digital Marketing With Influencer Marketing Moderation On Scarlett Products - Abdul Malik; Marsianus Manto; Muhammad Rizki Akbar; Naufal Fajri (DPPM Universitas Pelita Bangsa, 2024)
This study aims to analyze the influence of promotion on purchasing decisions for Scarlett products through digital marketing, considering the moderating role of influencer marketing. The research method used is descriptive with a quantitative approach. Data were collected through questionnaires distributed to 97 respondents who had purchased Scarlett products. Data analysis was carried out using simple linear regression with the SmartPLS Version 4.0 program. The results of the study indicate that digital marketing has a positive and significant influence on purchasing decisions, while promotion does not have a significant direct influence on purchasing decisions. However, promotion has a very strong influence on digital marketing, which in turn positively influences purchasing decisions. In addition, influencer marketing has been shown to moderate the relationship between promotion and purchasing decisions, strengthening the influence of promotion on purchasing decisions through digital marketing. These findings indicate the importance of integration between promotion, digital marketing, and influencer marketing in marketing strategies to improve consumer purchasing decisions